Factors affecting the profitability, productivity, and sustainability of socially disadvantaged urban agriculture operations in Pittsburgh, Pennsylvania - Hannah Whitley (Urban Food Systems Symposium, 2020)
Over the past twenty years, various initiatives and policy updates have encouraged sustainable agriculture production in cities across the United States, yet farmers and growers still face multiple environmental, economic, and social challenges unique to their urban context. This study used a mixed-method qualitative design to identify factors that affect the profitability, productivity, and sustainability of socially disadvantaged urban agriculture operations in Pittsburgh, Pennsylvania. Findings reveal four sets of factors that constrain sustainable agriculture production for socially disadvantaged growers in Pittsburgh: (1) Navigating institutions and support organizations; (2) Finding and maintaining community; (3) Environmental barriers and limitations; (4) Race, gender, and intersections of identity. Comparisons of participant demographic characteristics show that women growers ages 18-34, regardless of race, are more likely to struggle with navigating bureaucracy, finding mentors, accessing relevant information, and experience feelings of isolation compared to growers over age 35. This finding suggests that new and beginning urban growers struggle to navigate the complex systems of non-profit, extension, and federal support programs and organizations in place to support Pittsburgh’s agriculturalists. This study has also identified the need for citywide education and extension programming that meets the unique circumstances of urban growers, such as workshops and training that describe best practices for soil remediation, marketing, and distribution strategies for small-scale farms and gardens. This research provides essential insight into critical urban agriculture scholarship and encourages discussion concerning the strengths and shortcomings of existing urban agriculture support services and opportunities for improvement among existing non-profit organizations, government agencies, research institutions, and extension services.
Keywords: historically marginalized farmers; qualitative methods; sustainable agriculture